MODEL OF AIRCRAFT AVIATION EVENT LOCATION - Запорожець, О. І.; Ахмед, Хайдар Хосейн (Proceedings of National Aviation University (archive), 2021)
The model of the place of the aviation event through the distribution function is determined, provided that its parameters depend on the flight stage.